Combinational Design of Electronic Structure and Nanoarray Architecture Achieves a Low‐Overpotential Oxygen Electrode for Aprotic Lithium–Oxygen Batteries. Issue 3 (23rd December 2019) - Xiao, Liang; Yi, Jingyu; Kou, Zongkui; Li, Erwei; Deng, Bohua; Wang, John; Liu, Jinping
Abstract: Transition metal nitrides (TMNs) are generally recognized as excellent electrocatalysts in aqueous solution because of their distinct electronic structures and high electrical conductivity. However, their potential catalytic activities are rarely studied in the oxygen electrodes of aprotic lithium–oxygen batteries and the intrinsic electroactivities are quite difficult to be manifested in binder‐involved electrodes. Herein, a novel combinational design of electronic structure and nanoarray architecture is proposed to eliminate the influences of binders and additives and achieve high performance of TMNs as oxygen electrodes for aprotic lithium–oxygen batteries. In the case study of CoN nanowire arrays (NAs), experimental coupled with theoretical studies demonstrate that the distinct electronic structure of CoN enables the appropriate adsorption and facile charge transfer between the discharge product Li2 O2 and CoN. Results also show that the nanoarray architecture of CoN enables the full utilization of catalytic active sites, efficient mass transportation, and sufficient inner spaces for accommodating the insoluble discharge product. Thus, the CoN NA cathode achieves both a low overall overpotential of 1.01 V and a high areal capacity of 3.35 mA h cm −2 . The combinational design principle of electronic structure and electrode architecture provides a promising way to develop advanced oxygen electrode for metal–air batteries. Abstract : Combinational design of electronic structure and nanoarray architecture enables the optimal adsorption, facile charge transfer, and conformal growth of Li2 O2 on a CoN 3D electrode. With such an efficient cathode, an aprotic lithium–oxygen battery is assembled, exhibiting both a low overall overpotential of 1.01 V and a high areal capacity of 3.35 mA h cm −2 .